Sectoral shockwaves: examining Bursa Malaysia's sector indices amid the COVID-19 pandemic - Dellow, Alyssa April; Bahaludin, Hafizah (MMU Press, 2026)
The Coronavirus disease 2019 (COVID-19) outbreak is becoming a widespread concern, as it is causing a decline in economies and negatively impacting stock markets worldwide. As the Malaysian government implements the Movement Control Order (MCO) to curb the spread of the deadly virus, the Malaysian stock market is rapidly impacted, becoming volatile and unpredictable throughout the pandemic phase. Thus, this study aims to analyse the structural correlation patterns of the Bursa Malaysia Sectoral Index Series using the threshold network approach. The data utilised in this study are the closing prices of all 13 sectoral indexes, spanning from January 1, 2019, to December 31, 2021. Threshold networks are constructed for the years 2019, 2020, and 2021 based on different threshold values to visualise the correlation between indexes. The results suggested that COVID-19 affected the Malaysian stock market, as the indexes appeared to be more correlated with each other in 2020. In addition, consumer products and services (KLCM), industrial products and services (KLIP), property (KLPR), and construction (KLCT) emerged as the most influential indexes throughout the pandemic. This study will help market participants gain an understanding of the correlation between indexes based on threshold networks.